ENHANCING CIVIC LITERACY IN PRIMARY EDUCATION THROUGH AND TEAM GAMES TOURNAMENT: A BIBLIOMETRIC REVIEW (2015–2025) - Pranata, Alvira; Syamsijulianto, Tri (Universitas Muhammadiyah Lamongan, 2025)
Civic literacy is a critical competency for primary education, fostering students’ understanding of societal roles, rights, and responsibilities. However, traditional teaching methods often struggle to engage young learners effectively in this domain. This study aims to explore the enhancement of civic literacy through innovative pedagogical strategies, specifically Game-Based Learning (GBL) and Team Games Tournament (TGT), by conducting a bibliometric review of relevant literature from 2015 to 2025. The method involved systematic data collection from academic databases, followed by quantitative and qualitative bibliometric analyses to identify research trends, influential works, and thematic developments related to GBL and TGT in civic education. Results reveal an increasing scholarly interest in applying GBL and TGT as engaging, interactive, and collaborative approaches that promote critical civic competencies among primary school students. Key findings highlight the positive impact of these methods on student motivation, teamwork skills, and civic knowledge acquisition. Despite promising outcomes, gaps remain in long-term impact studies and cross-cultural applicability. In conclusion, this review underscores the potential of integrating GBL and TGT in primary education to effectively foster civic literacy, encouraging further empirical research and practical implementation tailored to diverse educational contexts.